2020
DOI: 10.1007/s11837-020-04436-6
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Quantification in Atomistic Modeling of Metals and Its Effect on Mesoscale and Continuum Modeling: A Review

Abstract: The design of next-generation alloys through the Integrated Computational Materials Engineering (ICME) approach relies on multi-scale computer simulations to provide thermodynamic properties when experiments are difficult to conduct. Atomistic methods such as Density Functional Theory (DFT) and Molecular Dynamics (MD) have been successful in predicting properties of never before studied compounds or phases. However, uncertainty quantification (UQ) of DFT and MD results is rarely reported due to computational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 100 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…This topic is the focus of the Integrated Computational Materials Engineering (ICME) domain, which has received enormous attention in recent years [12]. Research in ICME is inherently multi-scale, starting with molecular dynamics or CALPHAD (CALculation of PHAse Diagrams) simulations for nano-scale properties [13,14]. Results become inputs for higher level models that compute micro-scale properties, ending with continuum models that can be used for macro-scale simulations.…”
Section: Design With As-manufactured Propertiesmentioning
confidence: 99%
“…This topic is the focus of the Integrated Computational Materials Engineering (ICME) domain, which has received enormous attention in recent years [12]. Research in ICME is inherently multi-scale, starting with molecular dynamics or CALPHAD (CALculation of PHAse Diagrams) simulations for nano-scale properties [13,14]. Results become inputs for higher level models that compute micro-scale properties, ending with continuum models that can be used for macro-scale simulations.…”
Section: Design With As-manufactured Propertiesmentioning
confidence: 99%
“…. , d where j ą 0, with e j as defined in equation (9). In other words, in an admissible index set, all indices with smaller entries in at least one direction are also included in the set.…”
Section: Dimension-adaptive Multi-index Monte Carlomentioning
confidence: 99%
“…Given the critical importance of UQ for a wide variety of problems in materials science, several frameworks have been developed to provide robust predictions under uncertainty, see e.g., [5,6,7]. Comprehensive reviews of UQ applications in ICME-based simulations can be found in Honarmandi and Arróyave [8], Gabriel et al [9], and Acar [10]. For example, Zhao et al [11] incorporated measurement and parametric uncertainty to quantify the uncertainty of critical resolved shear stress for hexagonal close-packed (HCP) Ti alloys from nano-indentation.…”
Section: Introductionmentioning
confidence: 99%
“…It is an obstacle for CC to stand on par with, or to replace, physical measurements 8 or to be used in decision making 9 . It has also a strong impact in multi-scale simulation, where propagation of uncertainty through the scales is necessary to assess the reliability of predictions [10][11][12] , or in iterative learning to minimize the cost of high-level calculations [13][14][15] . In benchmarking, a very sensible way to select among a set of levels of theory would be to pick one with a fit-to-purpose PU.…”
Section: Introductionmentioning
confidence: 99%